Working Condition, Problems and Its Impact on the Health of Sexual and Gender Minorities (Shiksha Shastra Saurabh, 2018)
The third gender in contemporary societies is viewed from different angle. They have been facing different problems because of their sexuality. The objective of the paper is to explore the working condition, problems and its impact on the health of sexual and gender minorities in community. The descriptive research design was adopted in this study. It was based on field study in Kathmandu valley. Interview schedule has been applied as tool of data collection. The study was delimited to the LGBTI registered under BDS only. Altogether 100 respondents were selected out of total (111) purposively. Most of the LGBT (53.6%) were involved in private sector and 34.56% were working as sex worker. The respondents (38.47%) reported that they were dismissed from the job and 12.5% suffered from sexual exploitation and rape. Similarly, 32.78% suffered from mental tension and 20% suffered from depression. Social support, information education and awareness programs targeting the LGBT and studies covering a diverse population are recommended.